2017
DOI: 10.1103/physrevd.96.074008
|View full text |Cite|
|
Sign up to set email alerts
|

Hard photoproduction of a diphoton with a large invariant mass

Abstract: The electromagnetic probe has proven to be a very efficient way to access the $3-$dimensional structure of the nucleon, particularly thanks to the exclusive Compton processes. We explore the hard photoproduction of a large invariant mass diphoton in the kinematical regime where the diphoton is nearly forward and its invariant mass is the hard scale enabling to factorize the scattering amplitude in terms of generalized parton distributions. We calculate unpolarized cross sections and the angular asymmetry trigg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 42 publications
(22 reference statements)
1
15
0
Order By: Relevance
“…[7,8] at high energy, and a similar strategy has also been advocated in ref. [9][10][11][12]. 2 The absence of any pinch singularity has been proven for cases which involves at least one photon [14].…”
Section: Introductionmentioning
confidence: 98%
“…[7,8] at high energy, and a similar strategy has also been advocated in ref. [9][10][11][12]. 2 The absence of any pinch singularity has been proven for cases which involves at least one photon [14].…”
Section: Introductionmentioning
confidence: 98%
“…After a first rich crop of experimental data [1], it becomes clear [2] that trustable information on the quark and gluon 3−dimensional content of hadrons needs to gather experimental data from a set of reactions not restricted to the simplest ones (spacelike, timelike or double DVCS on the one hand, exclusive meson electroproduction on the other hand). After a Born order study [3,4] which demonstrated its phenomenological interest, we thus studied, at next to leading order (NLO) in the QCD coupling constant α s , the photoproduction of a large mass diphoton on a nucleon target…”
Section: Introductionmentioning
confidence: 99%
“…We use dimensional regularization as the main tool of our proof. Let us first outline the results of the LO study for photoproduction [3] and electroproduction [4]. Due to charge parity constraint, the contributing GPDs at any order in α s are the chargeodd quark GPDs (which are not accessed by DVCS) and there is no gluon GPD contribution.…”
Section: Introductionmentioning
confidence: 99%
“…The exclusive photoproduction of two photons on a unpolarized proton or neutron target γ(q, ε) + N(p 1 , s 1 ) → γ(k 1 , ε 1 ) + γ(k 2 , ε 2 ) + N (p 2 , s 2 ) , (1.1) in the kinematical regime of large invariant diphoton mass M γγ of the final photon pair and small momentum transfer t = (p 2 − p 1 ) 2 between the initial and the final nucleons, has a number of interesting features [1]. First, it is a purely electromagnetic process at Born order -as are deep inelastic scattering (DIS), deeply virtual Compton scattering (DVCS) and timelike Compton scattering (TCS) -and, although there is no deep understanding of this fact, this property is usually accompanied by early scaling.…”
Section: Introductionmentioning
confidence: 99%